Independent origin of large labyrinth size in turtles - Serjoscha W. Evers; Walter G. Joyce; Jonah N. Choiniere; Gabriel S. Ferreira; Christian Foth; Guilherme Hermanson; Hongyu Yi; Catherine M. Johnson; Ingmar Werneburg; Roger B. J. Benson (Nature Communications, 2022)
The size and shape of the inner ear, or bony labyrinth, is thought to be related to ecological adaptations in vertebrates. Here, the authors examine this relationship in turtles across 230 million years of evolution, unexpectedly finding large labyrinth size and no association with ecology.